Pengaruh Stres Kerja, Insentif Dan Lingkungan Kerja Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagai Variabel Mediasi - Nur Ita Ariansy; Marlina Kurnia (Universitas Muhammadiyah Magelang, 2022)
This study aims to examine and analyze the effect of work stress, incentives and work environment on employee performance with job satisfaction as a mediating variable. The analysis tool used multiple linear regression with SPSS 25. The sampling method was using porposive sampling and obtained 52 respondents. The results showed that job stress and job satisfaction had a negative and insignificant effect on employee performance. While incentives have a positive and insignificant effect on employee performance, the work environment has a positive and significant effect on employee performance. Then, job stress has a negative and insignificant effect on job satisfaction, incentives have a positive and significant effect on job satisfaction, the work environment has a positive and significant effect on job satisfaction and job satisfaction mediates the effect of job stress and the environment on employee performance, while job satisfaction does not mediate the effect. incentives on employee performance.